Euro-par 2011 parallel processing 17th international conference, Euro-Par 2011, Bordeaux, France, August 29-September 2, 2011, proceedings, part II - International EURO-PAR Conference 2011 Bordeaux, France); Jeannot, Emmanuel; Namyst, Raymond; Roman, Jean.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
The two-volume set LNCS 6852/6853 constitutes the refereed proceedings of the 17th International Euro-Par Conference held in Bordeaux, France, in August/September 2011. The 81 revised full papers presented were carefully reviewed and selected from 271 submissions. The papers are organized in topical sections on support tools and environments; performance prediction and evaluation; scheduling and load-balancing; high-performance architectures and compilers; parallel and distributed data management; grid, cluster and cloud computing; peer to peer computing; distributed systems and algorithms; parallel and distributed programming; parallel numerical algorithms; multicore and manycore programming; theory and algorithms for parallel computation; high performance networks and mobile ubiquitous computing.
Electronic reproduction.
Keywords: Parallel processing (Electronic computers) -- Congresses; Parallel programming (Computer science) -- Congresses; Electronic data processing -- Distributed processing -- Congresses; Electronic books